Organ Sonatas and Solos [de Wolfgang Amadeus Mozart] = Kirchensonaten, Orgelwerke [de Wolfgang Amadeus Mozart] = La musique pour orgue, sonates et solos [de Wolfgang Amadeus Mozart] = Sonate da chiesa, opere per organo [de Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: Sonatas da Chiesa Nº 1-17: KV 67, KV 68, KV 69, KV 144, KV 145, KV 212, KV 224, KV 225, KV 241, KV 244, KV 245, KV 263, KV 274, KV 278, KV 328, KV 329, KV 336; Adagio and Allegro in F Minor, KV 594; Fantasia in F Minor, KV 608; Andante in F, KV 616.